Exploring natural ventilation strategies in Javanese vernacular houses for sustainable design - Mohamad Muqoffa; Suyitno; Indri Yaningsih; Rendy Adhi Rachmanto; Kesit Himawan; Novi Caroko; Basuki (Journal of Asian Architecture and Building Engineering)
This study investigates natural ventilation strategies in Javanese vernacular houses to enhance sustainable building design tailored to local climates and promote comfort and environmental sustainability in Javanese communities. It examines adaptations of these strategies in rural (Saradan) and urban (Laweyan) contexts using a comprehensive methodology comprising document analysis, literature review, stakeholder interviews, and case studies. Insights from classical texts and architectural records inform traditional values and principles related to energy sustainability, supplemented by perspectives gathered through interviews with homeowners, architects, and cultural experts on integrating local values into sustainable practices. The findings reveal that in Saradan’s rural areas, expansive layouts and natural elements effectively facilitate natural ventilation, utilizing large courtyards and strategically positioned windows to optimize airflow and thermal comfort. In contrast, Laweyan’s urban setting employs compact designs with smaller openings and internal courtyards to manage airflow and mitigate heat accumulation. The study illustrates how traditional Javanese architectural practices adapt to contemporary contexts, supporting energy efficiency and occupant well-being while reconciling technological advancements with cultural heritage preservation. It offers insights for architects, researchers, and policymakers to develop guidelines and innovations that optimize Javanese ventilation strategies across diverse climatic conditions and explore their socio-economic impacts.